Physicochemical Factors Drive Bacterial Communities in an Aquaculture Environment - Sun, Fulin; Wang, Chunzhong; Yang, Hongqiang (Frontiers in Environmental Science, 2021)
The role of microbial ecology in aquaculture is becoming increasingly significant; however, studies on the changes in microbial ecology driven by the culture environment are limited. In the present study, high-throughput sequencing and chemical analysis was used to explore changes in environmental parameters, bacterial community structure, and their relationships between a water source (Bay) and an aquaculture area located in a reclaimed area. Statistical analysis results revealed that OTUs (operational taxonomic units) levels in inlet water and pond water varied significantly (p < 0.05). Non-metric multidimensional scaling (NMDS) analysis revealed the distribution characteristics of bacterial community structure with water properties. The abundance of Alphaproteobacteria, Actinobacteria, and Flavobacteria in pond water increased significantly when compared to in inlet water. The abundance of heterotrophic bacteria, such as Candidatus Actinomarina, Candidatus Aquiluna, Marivita, and Vibrio species in pond water was significantly higher (Welch's t-tests , p < 0.05) than inlet water. Functional prediction analysis primarily revealed an increase in the function that was associated with carbon and nitrogen metabolism in the pond environment. Canonical correlation analysis revealed that the bacterial community structure was predominantly influenced by inorganic nutrients. Nitrate-nitrogen (N), nitrite-N, ammonium-N, and phosphate-phosphorous (P) were the key factors influencing bacterial community structure in pond environment. A significant correlation was observed between inorganic N and phosphorus (P), and dominant bacterial genera (p < 0.05), demonstrating the potential mechanism of regulation of nutrients in bacterial communities. The present study described the microbial ecology of aquaculture ponds in detail and provides a scientific basis for the management of aquacultural environments.